2017
DOI: 10.1111/ijn.12578
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in nursing students and related factors: A cross‐sectional study

Abstract: Anxiety, depression, irregular bedtime, and lower socio-economic situation are factors that make falling asleep difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
5
15
1
1
Order By: Relevance
“…A survey conducted in India points out that the depressive symptoms are more intense during the first year of the course, decreasing gradually from this period on (1) . However, cross-sectional studies carried out in Malaysia and China and a exploratory-descriptive study conducted in Brazil corroborate these findings when revealing that these symptoms are more severe in the last periods of the course (3,14,18) . Such a divergence in the literature can be explained by cultural, social and economic differences between these countries and by the way the course is structured, its curriculum and workload, for example, are factors that vary according to the university and society in question.…”
Section: Discussionmentioning
confidence: 77%
“…A survey conducted in India points out that the depressive symptoms are more intense during the first year of the course, decreasing gradually from this period on (1) . However, cross-sectional studies carried out in Malaysia and China and a exploratory-descriptive study conducted in Brazil corroborate these findings when revealing that these symptoms are more severe in the last periods of the course (3,14,18) . Such a divergence in the literature can be explained by cultural, social and economic differences between these countries and by the way the course is structured, its curriculum and workload, for example, are factors that vary according to the university and society in question.…”
Section: Discussionmentioning
confidence: 77%
“…There must be enough resources to help school nurses assist other school employees to de-escalate the impact of anxiety among students and one way to do this is to create a partnership among community members and school officials (Smith-Fromm and Evans-Agnew, 2017). It was found that anxiety have a direct effect on the sleeping pattern and quality of sleep of nursing students based on a survey conducted to 379 nursing students at a University in Western Anatolia, Turkey between 2014 and 2015 (Gunes and Arslantas, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Choueiry 13 en un estudio realizado en el Líbano en universitarios, demostró que la ansiedad Pág. 25 clínicamente significativa es más frecuente entre los estudiantes que manifiestan insomnio (p=0.006); además, Günes 14 demostró que la ansiedad no solo afecta la calidad del sueño sino también incrementa la gravedad del insomnio e incluso predispone al desarrollo de trastornos afectivos como la depresión. Así mismo, Kirwan 15 sostiene que la dificultad para el manejo de la ansiedad entre estudiantes universitarios de diferentes carreras supone el incremento de la severidad de los trastornos del sueño, específicamente, del insomnio (p =0.001).…”
Section: Discussionunclassified